2008
DOI: 10.1002/ajmg.a.32286
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation genetic diagnosis for complex chromosome rearrangements

Abstract: Complex chromosome rearrangements (CCR) are structural rearrangements that involve more than two breakpoints. The most common ones involve three chromosomes and three breakpoints, but double translocations can also occur. Theoretically, the potential for chromosome imbalance in the gametes of CCR carriers is higher than for simple translocations, and thus they are at an even higher risk of recurrent miscarriage. Preimplantation genetic diagnosis (PGD) has been shown to significantly reduce the risk of repeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…Escudero et al [5] reported two normal/balanced embryos out of 22 diagnosed in a three-way translocation carrier. The couple achieved pregnancy and delivery of a child after five PGD cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Escudero et al [5] reported two normal/balanced embryos out of 22 diagnosed in a three-way translocation carrier. The couple achieved pregnancy and delivery of a child after five PGD cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who carry a balanced translocation or inversion are known to have high rates of unbalanced gametes following meiotic segregation and are at great risk of producing embryos with unbalanced chromosome complements. These chromosome imbalances can lead to high rates of miscarriage, decreased fertility, and in some cases, the birth of children affected by congenital aberrations [Escudero et al 2008;Treff et al 2011].…”
Section: Introductionmentioning
confidence: 99%
“…According to the structure of the rearrangement, CCRs can be categorised into four main types (Escudero et al 2008, Gruchy et al 2010, Kang et al 2010, Pellestor et al 2011a, Madan 2012. The first type is the simplest in structure and includes an equal number of breakpoints and of chromosomes involved in the CCR, a so-called three-way rearrangement with three non-homologous chromosomes with one breakpoint each.…”
Section: Introductionmentioning
confidence: 99%
“…Such a high frequency indicates an increased risk of reproductive failure, such as miscarriages (50-100%) (Batista et al 1994). Moreover, only 5-10% of CCRs are recognised de novo in prenatal diagnosis (Giardino et al 2006, Escudero et al 2008, Lim et al 2008). In such cases, an estimated value of 3.5% per every chromosome breakpoint in CCRs has been adapted as a reliable and predictable value for the determination of the risk factor in offspring (Madan 2012).…”
Section: Introductionmentioning
confidence: 99%